i just read somwhere that(adsbygoogle = window.adsbygoogle || []).push({});

if cos a = cos d

then a=2n(pi)±d where n is integer

So, if cos (b*ln (i/j))= cos (-b (lni/j))=cos(b*ln(j/i))

can i write

b*ln i/j = 2n(pi)±b*ln(j/i)

or

bln(j/i)+bln(i/j)=2n(pi) or 2n(pi)=0

b=n(pi)/(ln(i/j)-ln(j/i))=n(pi)/(b*ln(i/j))

then replace b in

cos(b*lni/j)=cos(n(pi))= ±1

I feel that something is wrong. But what?

**Physics Forums - The Fusion of Science and Community**

# I just read somwhere thatif cos a = cos dthen a=2n(pi)±d where

Have something to add?

- Similar discussions for: I just read somwhere thatif cos a = cos dthen a=2n(pi)±d where

Loading...

**Physics Forums - The Fusion of Science and Community**